Analysis of Determinants of Employee Performance through Job Satisfaction and Organizational Commitment (Case Study of PT. Hadji Kalla, Urip Sumoharjo Branch) - Tiong, Piter; Soemaryo, Partono (International Journal of Management and Business Intelligence, 2024)
This research seeks to examine the influence of self-efficiency and locus of control on job satisfaction, organizational commitment and employee performance. It also aims to explore the relationship between job satisfaction, organizational commitment, and employee performance. by growing satisfaction and organizational commitment at PT. Haji Kalla Urip Sumoharjo Branch. The research focused on 163 employees who worked in the sales and used car dept of PT. Haji Kalla Urip Sumoharjo Branch. The sampling method uses saturated sampling. Questionnaires were used to collect data, which was then analyzed using path analysis on Amos version 24 software. Research findings prove that self-efficacy has a real impact on job satisfaction, organizational commitment and employee performance. Job satisfaction significantly improves employee performance and organizational commitment. The results of the mediation test show that there is quite a large mediating influence on the relationship between self-efficacy and employee performance, as well as between locus of control and employee performance at PT. Hadji Kalla Urip Sumoharjo Branch. This study shows that self-efficacy, job satisfaction, and organizational commitment collectively mediate around 46.80% of the impact of self-efficacy on employee performance. In addition, locus of control, job satisfaction, and organizational commitment mediate 28.20% of the impact of locus of control on employee performance.